The Effect of Tax Morals and the Digitalized Tax System on Tax Compliance with Trust in the Government as a Moderating Variable - Sulistyono, Henry; Ratna Mappanyukki (Dinasti International Journal of Digital Business Management, 2023)
The purpose of this research was to determine the effect of tax morale and tax digitalization system on tax compliance with trust in government as a moderating variable. The population in this study are corporate taxpayers in the Cikarang-Cibitung Industrial Area. In this study the data analysis technique used was quantitative using the PLS-SEM (Structural Equation Model) or structural equation model. The results of this research were Tax Morale has no effect on Taxpayer Compliance, The Tax Digitization System has a positive influence on Taxpayer Compliance, Trust in the Government in this study cannot act as a moderating variable in the Tax Morale variable on Taxpayer Compliance, and Trust in the Government in this study cannot act as a moderating variable in the Tax Digitalization System variable on Taxpayer Compliance.